Prevention of Violence, Neglect and Exploitation of Children Reviewed from Law Number 35 of 2014 Concerning Child Protection - Anggriani, Jum; Indah Harlina; Ali Abdullah; Arifardhani, Yoyo; Andreas Sapta Finady (PT Inovasi Pratama Internasional, 2025)
Violence, neglect, and exploitation of children remain serious problems in Indonesia that require systematic prevention efforts based on law and community participation. This study aims to increase public understanding of the prevention of violence against children based on Law Number 35 of 2014 concerning Child Protection through a comprehensive community service program. The method used is a participatory and educational approach with a mixed qualitative-quantitative design, involving 255 participants consisting of 100 heads of families, 50 educators, 30 community leaders, and 75 children aged 10-17 years. Activities were carried out for 6 months at the village level through participatory workshops, intensive training, legal socialization, and the establishment of a community-based child protection forum. Data collection was carried out through pre-post test surveys, in-depth interviews, focus group discussions, and participant observation. The results showed a significant increase in participants' knowledge by 34% exceeding the minimum target of 25%, a positive attitude change in 89% of participants to report cases of child violence, and a participation rate of 92%. The establishment of a child protection forum with 35 members from various community elements and a strategic partnership network with relevant agencies demonstrates the program's success in building a sustainable protection system. Implementation faced challenges such as cultural resistance, limited infrastructure, and the community's socioeconomic conditions. The program successfully created a community-based child protection model that can be replicated in other regions with adaptations to local contexts to achieve a child-friendly Indonesia.